1996
DOI: 10.1111/j.1528-1157.1996.tb00510.x
|View full text |Cite
|
Sign up to set email alerts
|

Ictal Speech Manifestations in Temporal Lobe Epilepsy: A Video‐EEG Study

Abstract: To evaluate ictal speech manifestations in complex partial seizures (C PS), we reviewed videotapes of 68 consecutive patients who underwent anterior temporal lobectomy (ATL) for treatment of intractable epilepsy in Taiwan. In all, 261 CPS were collected from their video-EEG (VEEG) recordings. Cerebral speech dominance was determined by intracarotid injection of sodium amobarbital (Wada test) in all cases. Ictal speech manifestations, classified as verbalization or vocalization, occurred in 32 patients (47.1%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…Ictal speech occurred mainly during right temporal seizures as reported by others 18,34 suggesting nondominant temporal EA 18,26,35,36 . It seems to result of functional nondominant temporal lobe impairment by epileptic discharges and consequent hyperfunction of the dominant hemisphere for language 35 .…”
Section: Discussionmentioning
confidence: 67%
“…Ictal speech occurred mainly during right temporal seizures as reported by others 18,34 suggesting nondominant temporal EA 18,26,35,36 . It seems to result of functional nondominant temporal lobe impairment by epileptic discharges and consequent hyperfunction of the dominant hemisphere for language 35 .…”
Section: Discussionmentioning
confidence: 67%
“…1,2,4 This lateralization also seems to apply to foreign language ISA as suggested by our three patients who all had right (nondominant) TLE, and by the two other studies that reported FLISA in a total of five unilingual patients who all had right TLE. 6,7 Intracerebral EEG data were available in only one of these five other patients, and demonstrated hippocampal seizure onset. 7 However, as directly confirmed by the authors of this study, no electrode was implanted in the amygdala.…”
Section: Resultsmentioning
confidence: 96%
“…[2][3][4][5] Foreign language ISA (FLISA) is a rare phenomenon that has been reported in only five unilingual right-handed men so far, all of whom had right TLE. 6,7 We report three additional French unilingual right-handed men who presented English spoken and emotionally salient ISA, benefited from an extensive intracerebral EEG investigation showing right amygdala seizure onset, and achieved long-term seizure freedom following right temporal lobectomy. Our data, together with previous reports, suggest that FLISA are generated by an epileptic network centered over the nondominant amygdala, and reflect the specific sexual dimorphism described in that structure for emotional processing.…”
mentioning
confidence: 97%
“…The presence or absence of speech is Downloaded by [New York University] at 13:56 21 July 2015 important. If speech occurs during the seizure, the seizure focus lateralizes to the nondominant hemisphere (most often the right hemisphere) (Yen et al 1996). Conversely, postictal aphasia or dysphasia points to involvement of the dominant hemisphere (most often the left hemisphere) (Gabr et al 1989).…”
Section: Clinical Featuresmentioning
confidence: 98%